Describing the impact of using task-shifting approaches in mental-healthcare: A quantitative study of mental health care professionals using questionnaires - Shongwe, Noxolo Precious (The IIE, 2020)
Task shifting is the name given to a process of delegation whereby tasks are moved, where appropriate, to less specialized health workers (WHO, 2008). The mental health care sector in South Africa has a treatment gap between people who need mental healthcare and those who receive it. Various strategies are being implemented to close the treatment gap however they are not long-lasting solutions. Task-shifting is an approach that has successfully worked in combating HIV/AIDS across low- and middle-income countries. This study was done to find out what perceptions mental health care workers have about the task-shifting approach. Key themes that were explored during the study include: low- and high-level mental health care workers, history of task-shifting, mental health care funding and the service pyramid model and COM-B model. Quantitative research was done by using a cross sectional design, an online survey was sent out to twenty participants working in the Mpumalanga province. Data was gathered through the Google docs platform and analysed by using descriptive statistics. The findings showed that mental health care professionals have a positive perception about the approach and are not opposed to it being fully implemented in the mental health care sector and not just in community psychology.
Keywords: Task-shifting approaches; Mental-healthcare; Healthcare professionals; South Africa